Utilization Setting Menu To Build Company Accounting System In Web Based Accounting Online System - Sunarya, Po. Abas; Saptoro, Arief; Peh, Zucheng (APTISI Transactions on Management (ATM), 2017)
In building a company, which needs to be disclosed by the information system, because to obtain the results of a company can use a system that can display financial information on the company. In the era of the modern era has been developing online web-based accounting, where employees can access information systems wherever and whenever located with an internet connection. The registration of new companies using the WBAOS system is very important to advance the system on the company. After registering the company account the company administrator is responsible for making the information online. By adding and modifying the company's customer information or accountant can see the company's information such as a bank, a currency that can be used again. Data or information that can be provided at this time. Then the information can be more up to the customer and also can more easily carry out their duties. The use of the settings menu to set the start of the company using WBAOS 2.0 (Web-Based Accounting Online System) can make it easier for administrators to prepare data or company information.